The effect of student based learning work sheet on material structures and networks on animals against motivation of students of SMAN 1 Labuhanhaji Timur regency of South Aceh - Yanizar Yanizar; Hasanuddin Hasanuddin; M. Ali S. (Jurnal Edubio Tropika, 2018)
This study aims to determine the effect of PBL-based LKPD on the material structure and function of tissue in animals on learning motivation and learning outcomes cognitive learners SMAN 1 Labuhanhaji East. The data retrieval took place in September 2016, with true experiment method with pre-test post-test, control group design which was held in SMAN 1 Labuhanhaji Timur, in the odd semester of academic year 2016/2017. This research was conducted in two classes namely XI IPA 1 as control class and XI IPA 2 as experiment class. Data was collected by questionnaire of motivation, to see the influence of LKPD based on PBL on learning motivation with t-test technique at significant level 0,05. The test results were performed to look at the homogeneity and normality of the data and show that the data is homogeneous and normally distributed. The result of t test shows that thitung ttabel is learning motivation value 3,465 1,685. Conclusion there is the influence of LKPD based on PBL on learning motivation of learners on the material structure and function of tissue in animal in SMAN 1 Labuhanhaji East Aceh Selatan.Keywords: Student Work Sheet, Problem Based Learning Model, Learning Motivation, Structure andNetwork on Animals.